Drivers of energy consumption in Kuwaiti buildings: Insights from a hybrid statistical and building performance simulation approach. (March 2021) - Azar, Elie; Alaifan, Bader; Lin, Min; Trepci, Esra; El Asmar, Mounir
Abstract: Understanding and quantifying the drivers of energy consumption in buildings is an essential step to identify inefficiencies and guide energy conservation efforts and policies. While such efforts are common in western countries, they remain limited in the Middle East and North Africa (MENA) region, particularly in the State of Kuwait. This article presents the first systematic assessment of the drivers of energy consumption in Kuwaiti commercial and residential buildings. It presents a unique hybrid study approach combining data collected from 463 buildings with Building Performance Simulation (BPS) developed and validated to mimic the performance of archetype (i.e., typical) Kuwaiti buildings. Results identify the built-up area and the thermostat cooling setpoints as the main determinants of electric consumption, quantifying the exact relationships between these variables. For instance, a simple 2 °C increase in the thermostat cooling setpoint can lead to a more than 10% reduction in total energy use. Other parameters that are typically known to affect building performance, such as the type of Air Conditioning (AC) systems installed, did not show statistically significant effects. The findings helped derive important recommendations for the Kuwaiti authorities, covering the educational, technological, and policy-related dimensions of the challenges facing the building sector. Highlights: Drivers of energy consumption in Kuwaiti buildings are mapped and quantified. The proposed approach combines statistical methods and building energy modeling. 463 buildings are surveyed, 3 energy models of archetype buildings are developed. Built-up area and thermostat setpoints are key drivers, outweighing design features. Recommendations are made covering education, technology, and energy policies.